183k views
0 votes
Use the integer tiles to evaluate the following expressions. 6 + 3 = 6 + (–4) = 6 + (–6) =

User Hrunting
by
5.0k points

2 Answers

7 votes

Answer:

1=9

2=2

3=0

Explanation:

User Anmari
by
5.3k points
7 votes

Given:

The expressions are:


6+3


6+(-4)


6+(-6)

To find:

The value of given expression by using integer tiles.

Solution:

We have,


6+3

Here, both number are positive. When we add 6 and 3 positive integer tiles, we get 9 positive integer tiles as shown in the below figure. So,


6+3=9

Similarly,


6+(-4)

Here, 6 is positive and -4 is negative. It means we have 6 positive integer tiles and 4 negative integer tiles.

When we cancel the positive and negative integer tiles, we get 2 positive integer tiles as shown in the below figure. So,


6+(-4)=2


6+(-6)

Here, 6 is positive and -6 is negative. It means we have 6 positive integer tiles and 6 negative integer tiles.

When we cancel the positive and negative integer tiles, we get 0 integer tiles as shown in the below figure. So,


6+(-6)=0

Therefore,
6+3=9, 6+(-4)=2,6+(-6)=0.

Use the integer tiles to evaluate the following expressions. 6 + 3 = 6 + (–4) = 6 + (–6) =-example-1
User Mark Pauley
by
4.4k points